1999
DOI: 10.1079/095442299108728875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phyto-oestrogens on tissues

Abstract: Recent investigations on the effects of phyto-oestrogens on various tissues have revealed that these diverse molecules may improve human health, particularly by protecting against certain chronic diseases. After a brief examination of the food sources, structures, and general cellular actions of the major phyto-oestrogens, current research ®ndings on cardiovascular disease, skeletal tissues, and reproductive cancers are reviewed. Phytooestrogen concentrations in blood may be maintained at high levels in those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(82 citation statements)
references
References 169 publications
1
79
0
2
Order By: Relevance
“…The character of having thick cortex in male quail embryonic gonad after exposure to exogenous estrogens is called "ovotestis" (Perrin et al, 1995;Berg et al, 2001;Oshima et al, 2012). It has been reported that a number of ER in germinal epithelial cells were increased by phytoestrogen (Anderson et al, 1999). This suggests that ER is involved in proliferation of germinal epithelial cells of the embryonic gonads.…”
Section: Discussionmentioning
confidence: 87%
“…The character of having thick cortex in male quail embryonic gonad after exposure to exogenous estrogens is called "ovotestis" (Perrin et al, 1995;Berg et al, 2001;Oshima et al, 2012). It has been reported that a number of ER in germinal epithelial cells were increased by phytoestrogen (Anderson et al, 1999). This suggests that ER is involved in proliferation of germinal epithelial cells of the embryonic gonads.…”
Section: Discussionmentioning
confidence: 87%
“…The investigations on the effects of phyto-oestrogens on various tissues have revealed that these diverse molecules may improve human health, particularly by protecting against certain chronic diseases [8]. It has also been reported that estrogen may have protecting effects against various cancers [9]- [10].…”
Section: Discussionmentioning
confidence: 99%
“…The oestrogenic isoflavones like genistein and biochanin-A may be broken down to the non-oestrogenic 4-ethyl-phenol and organic acids (Anderson et al, 1999). Ruminal microorganisms may take, however, 6 to 10 days to adapt fully to these substrates, so genistein may produce oestrogenic effects in sheep during the first few days after introduction of the phytoestrogenic diet.…”
Section: Discussionmentioning
confidence: 99%